Renewable Energy From the Ocean 1994
DOI: 10.1093/oso/9780195071993.003.0012
|View full text |Cite
|
Sign up to set email alerts
|

Open-Cycle OTEC

Abstract: The historical development leading to the proposal by Claude to generate power by producing steam in flash evaporation of warm seawater has been discussed in Chapter 2. In this chapter, the thermodynamic fundamentals of the open-cycle concepts are discussed, leading to a detailed review of state of the art and commercial prospects of the process. There are several variations on the standard OTEC open-cycle (OC) system. The three major variations are “hybrid cycle” (Bartone, 1978), “mist lift cycle” (Ridgway, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It was also found that steam generation was not constant over time, as the heater did not maintain a stable power level throughout the duration of the test. Based on the analysis of Figures 8 and 9, and the previous studies of Avery et al [4], the differences in the cooling relationships of each working fluid can be seen. In the case of R134a, the turbine inlet temperature must be 20 • C, and reduced in the condenser to 10 • C for condensation.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…It was also found that steam generation was not constant over time, as the heater did not maintain a stable power level throughout the duration of the test. Based on the analysis of Figures 8 and 9, and the previous studies of Avery et al [4], the differences in the cooling relationships of each working fluid can be seen. In the case of R134a, the turbine inlet temperature must be 20 • C, and reduced in the condenser to 10 • C for condensation.…”
Section: Resultsmentioning
confidence: 77%
“…Based on the analysis of Figures 8 and 9, and the previous studies of Avery et al [4], the differences in the cooling relationships of each working fluid can be seen. In the case Theoretical Rankine cycles were developed using thermodynamic equations [31] incorporating R134a and ammonia (see Figures 9 and 10).…”
Section: Selection Of the Working Fluidmentioning
confidence: 77%
See 2 more Smart Citations
“…It can be seen that the maximum width is around 4 km. Based on the climatological data, the San Andrés Island has an ideal temperature to implement an OTEC plant, in addition to the other necessary characteristics, such as a short distance between 1000 m deep and the coast, with a steep slope and a seabed without many reliefs, the location must have low waves (height less than 3.7 m), and ocean surface currents less than 1.5 m/s, and a low incidence of natural phenomena such as storms, earthquakes, hurricanes, among others [54].…”
Section: Otec System Locationmentioning
confidence: 99%